Avaliação dos músculos flexores e extensores de joelho de atletas de corrida, ciclismo e triatlo por dinamometria isocinética - Peres, Beatriz Da Silva [UNIFESP] (2019)
Objective: To evaluate and compare peak torque and knee muscle balance ratios, as well as the bilateral difference in the quadriceps and hamstring muscles among runners, cyclists, and triathletes of both genders. Methods: The isokinetic peak torque of quadriceps and hamstring muscles of 50 athletes (33 males and 17 females) were evaluated using an isokinetic dynamometer at 60 and 240º.s-1. The hamstring to quadriceps (H:Q) conventional balance ratio, H:Q functional ratio, and strength symmetry were calculated. Results: There was no difference in peak torque relative to the total body mass between the sports modalities, however, the male of the tree sports present values significantly higher (p < 0.05) than female. Female runners had a significantly higher H:Q functional ratio (1.7 ± 0.4) than male runners (1.3 ± 0.3) and female triathletes (1.3 ± 0.1) (p = 0.04). There was no difference in the H:Q conventional balance ratio among sports or between genders, since there was no bilateral asymmetry of the quadriceps and hamstring muscles. Conclusion: The H:Q functional ratio was higher in female runners than in male runners and female triathletes, which indicates a greater eccentric strength of the knee flexor muscles relative to the concentric force of the extensor muscles. The results exhibit in this present study can be used to direct works of strengthening and rehabilitation of runners, cyclists and triathletes.